Typology of Poverty Levels in Riau Province in 2023 - Emkhad Arif; Aswanto (Oikonomia : Journal of Management Economics and Accounting, 2024)
The typology in this research is a study of the classification and grouping of poverty levels based on macro poverty indicators, namely the Percentage of Poor Population (P0), Poverty Depth Level (P1), and Poverty Severity Level (P2). The aim of this research is to analyze the level of poverty in Riau Province based on districts/cities by grouping them based on poverty indicators (BPS Riau Province). Using cross section data in 2023. Meanwhile, the analysis methods used are descriptive analysis and cluster analysis. So, based on the results of the analysis, it can be concluded that the poverty of districts/cities in Riau Province is grouped into three groups with four districts/cities. Group 1 with the highest poverty rate is Meranti, Rohul, Pelalawan and Kuantan Singingi Islands. Group 2 with a moderate level of poverty is Indragiri Hulu, Bengkalis, Kampar and Rokan Hilir. Meanwhile, group 3 with a low poverty level is Pekanbaru, Dumai, Siak and Indragiri Hilir.